Pola Arus di Perairan Teluk Hurun Lampung Selatan - Riyadi, Agung (Jurnal Hidrosfir Indonesia, 2007)
We observed the current data in Hurun Bay, South Lampung Sumatra Hurun Bay is a small semi enclosed bay with areas up to 1.5 km2 and has four mouth river. Measuremet field around one year from Januari 2003 until Januari 2004. The two current sensor located at central of the bay and the sensor take a depth about four (4) and twelve (12) meter from surface.The continous current record indicated that the current in Hurun Bay relative small. The current velocity at June is higher and have a average value 3.98 cm/second at 4 meter and 3.94 cm/second at 12 meter from surface and commonly current velocity in bay under 50 cm/second. Keywords: pattern flow, teluk hurun, current velocity